Pan-European Analysis on Power System Flexibility - Marta Poncela (Energies, 2018)
Ongoing deployments of intermittent non-synchronous power generators (i.e., wind turbines and photovoltaics) challenge power (electricity) system security in terms of matching power generation and demand. Higher flexibility in the future generation fleet and power demand are likely to play an essential role in maintaining secure operation of the power system. This paper proposes a stepwise methodology based on a set of indicators for future power system flexibility analysis through assessing (i) flexibility requirements, (ii) available flexibility resources, and (iii) power system adequacy. The proposed methodology is applied to a European case for 2020 and 2025 scenarios. The insights gained from this study can be used as input in distributing power balancing resources and to introduce new balancing products in a power market. Benefits of the integrated energy market are presented.